A Sense of Viidu: The (Re)creation of Home by the Sri Lankan Tamil Diaspora in Australia - Kandasamy, Niro; Perera, Niru; Ratnam, Charishma; Sivanesan, Sumugan; Paramanathan, Gary; Pararasasingam, Paheerathan; Sanmuhanathan, Neeraja; Ratnamohan, Lux; Chandran, Shankari; Shakthidaran, S. (Palgrave Pivot, 2020)
This book is the first compilation of the experiences of the Sri Lankan Tamil diaspora in Australia. It explores the theme of home—from what is left behind to what is brought or (re)created in a new space—and all the complex processes that ensue as a result of leaving a land defined by conflict. The context of the book is unique since it focuses on the ten-year period since the Sri Lankan civil war ended in 2009. Although the war has officially come to an end, conflict continues in diverse and insidious forms, which we present from the point of view of those who have left Sri Lanka.